The role of Wnt/β-catenin signalling in the regulation of liver progenitor cell responses in non-alcoholic fatty liver disease - Shirolkar, Gayatri Dhananjay (Curtin University, 2021)
This study established a regulatory role for the Wnt/ß-catenin pathway in liver progenitor cells (LPCs) in cell culture and in vivo models of non-alcoholic fatty liver disease and demonstrated a significant potential for therapeutic targeting of LPCs with the Wnt inhibitor PRI-724 to inhibit chronic liver disease progression.